Усна теорія: підхід до студій у царині усної традиції - Фоули, Д. (Народна творчість та етнологія, 2012)
John Miles Foley. The Oral Theory: an Approach to Studies in Oral Tradition. The Oral Theory was initially created to solve the Homeric question. M. Parry proposed that the «author» of «Iliad» and «Odyssey» was actually the poetic tradition represented by a long series of individuals who owned the technique of oral-formulaic composition. Through the fieldwork conducted with A. Lord, aimed to check his hypothesis using the living South Slavic epic tradition. The Oral Theory was formulated by A. Lord. It became quickly popular in different countries. Just as the Oral Theory has helped to explain how preliterate singers composed their works, so now it will help to become a better audience to those compositions using the concept of traditional referentiality.